A facile and gentle method to fabricate NH4CoPO4 coating with superhydrophobic character study. (21st August 2019) - Zhang, Huaqiu; Lu, Yuwei; Jin, Xueyi; Wang, Bo; Yang, Tiantian; Xu, Huiwen; Liu, Hongtao; Chao, Chen
Abstract: In this paper, a NH4 CoPO4 coating is prepared on the surface of the Q235 steel by the method of chemical deposition and the modification of FAS-17. The SEM, XRD, FTIR and the contact angle measuring instruments are used to measure the chemical composition, topography, wetting properties, dynamic wetting process of the coating. The self-cleaning and the mechanical stability experiments are also conducted. The results show that the coating has a large number of corolla-shaped micro layered structure, which helps the surface achieve the property of superhydrophobic; the static contact angle of the coating reaches 153.5°, the rolling angle is 2°. The coating has both good self-cleaning capability and general mechanical wear resistance.